1994
DOI: 10.1093/ajcp/101.5.577
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometry:In Vitro Assessment of Its Potential Application for Diagnosis and Classification of Lymphoid Processes in Cytologic Preparations from Fine-needle Aspirates

Abstract: Detection and accurate classification of lymphoid processes in fine-needle aspirate specimens can be a challenging task for the pathologist. Recognizing the usefulness of flow cytometric methods for the diagnosis of lymphoproliferative disorders (LPDs), the authors applied flow cytometric analysis to 38 tissue samples that had a possible diagnosis of LPD and to fine-needle aspiration-derived cytologic preparations. Four aspirations from each sample provided from .44 x 10(6) to more than 70 x 10(6) cells in tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
1
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 0 publications
5
48
1
1
Order By: Relevance
“…In this setting we find FC preferable to immunohistochemistry, which is subject to more staining artifact and subjective interpretation. 7,27,28,41 This study confirmed the findings of previous studies 4,10,26,30,37,40 showing a high level of diagnostic accuracy (82%) when using FNAB with adjuvant FC. The addition of core biopsy to FNAB increased the diagnostic accuracy to 93% in our study.…”
Section: Discussionsupporting
confidence: 89%
“…In this setting we find FC preferable to immunohistochemistry, which is subject to more staining artifact and subjective interpretation. 7,27,28,41 This study confirmed the findings of previous studies 4,10,26,30,37,40 showing a high level of diagnostic accuracy (82%) when using FNAB with adjuvant FC. The addition of core biopsy to FNAB increased the diagnostic accuracy to 93% in our study.…”
Section: Discussionsupporting
confidence: 89%
“…Several more recent publications have reported much lower complication rates with smaller needle diameters (18 gauge or smaller) ( 5,6,16 ). Diseases that commonly affect the spleen can pose a diagnostic challenge to the clinician, radiologist, and pathologist, and the reported diagnostic accuracy of splenic biopsy varies, ranging between 84% and 90% ( 5,14,(16)(17)(18)(19)(20)(21).…”
Section: Search Strategymentioning
confidence: 99%
“…Three patients (36)(37)(38) were classified as lymphoplasmacytoid lymphoma (CD 5, CD 10 and CD 23 negative). All 3 cases were histologically typical mantle cell lymphoma.…”
Section: Flow Cytometry Diagnosis Of Nhlmentioning
confidence: 99%